PENGARUH KEMAMPUAN TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI KERJA (The Influence of Ability to Employee Performance Medicated by Work Motivation) - Awaluddin Awaluddin; Samdin Samdin; Yusuf Yusuf (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims: 1) to examine the effect of ability on motivation, 2) examine the effect of ability on employee performance, 3) examine the effect of motivation on employee performance, 4) examine the effect of ability on employee performance mediated by work motivation.The object of research is the North Konawe District Education and Culture Office. The study population was all employees in the Department of Education and Culture of North Konawe Regency, amounting to 95 people. Size of sample determination using census / saturation technique means that all populations are used as samples, thus the research sample is 95 people.Data collection methods using a questionnaire, the scale of data measurement using a Likert scale model. The research data were analyzed using path analysis with the help of smartPLS ver 2 software.The results of the study: 1) ability has a positive and significant effect on motivation, 2) ability has a positive and significant effect on employee performance, 3) motivation has a positive and significant effect on employee performance, 4) ability has a positive and significant effect on employee performance mediated by employee motivation. Keywords: ability, work motivation, employee performance